Adaptation and evaluation of a child-friendly patient reported outcome measure for use in Australia. Issue 1 (February 2021) - Bradford, Natalie K.; Chan, Raymond J.; Walker, Rick; Herbert, Anthony; Cashion, Christine; Tjondronegoro, Dian; Yates, Patsy
ABSTRACT: Background: Use of Patient Reported Outcomes (PROs) to assess symptoms in children are not routinely used in clinical practice, yet children with complex conditions experience a significant number of symptoms. Aim: To adapt and evaluate the Symptom Screening in Pediatrics Tool (SSPedi), a PRO measure developed in Canada for use with Australian children. Methods: SSPedi wording was adapted and item relevance assessed by an expert clinical group (N = 7) resulting in the Australian version (SSPedi-Aus). Cognitive interviewing with children with cancer (N = 10, 8–18 years) established understanding and difficulty with completing. A second group of child-parent dyads (N = 30) were recruited to evaluate psychometric properties (content validity, test-retest reliability, and parent-proxy) measured with Intraclass Correlation Coefficients (ICC) with 95% Confidence Intervals (CI). Acceptability and usefulness of SSPedi-Aus were also assessed. Findings: Construct validity was confirmed across all items by 30 children. Child test-retest achieved excellent concordance (ICC 0.98, 95% CI 0.91 to 0.99). Symptoms causing the most distress as reported by children were different to those identified by parents. Although children and parents returned a similar mean total score (13.43 vs. 13.80), there was weak overall interrater reliability (ICC 0.37, 95% CI −0.26 to 0.70, p = 0.12). Conclusion: Children are distressed by symptoms that may not be identified by parents or reported to clinicians, yet these symptoms are amendable to intervention. The SSPedi-Aus is useful to assess the level of distress caused by symptoms in children.